Mental Health: Philosophical Perspectives
XXII, 302 p.
Keywords: The concept 'health' is ambiguous [18,9, 11]. The concept 'mental health' is even more so. 'Health' compasses senses of well-being, wholeness, and sound ness that mean more than the simple freedom from illness - a fact appreci ated in the World Health Organization's definition of health as more than the absence of disease or infirmity [7]. The wide range of viewpoints of the con tributors to this volume attests to the scope of issues placed under the rubric 'mental health. ' These papers, presented at the Fourth Symposium on Philos ophy and Medicine, were written and discussed within a broad context of interests concerning mental health. Moreover, in their diversity these papers point to the many descriptive, evaluative, and, in fact, performative functions of statements concerning mental health. Before introducing the substance of these papers in any detail, I want to indicate the profound commerce between philosophical and psychological ideas in theories of mental health and disease. This will be done in part by a consideration of some conceptual developments in the history of psychiatry, as well as through an analysis of some of the functions of the notions of mental illness and health. 'Mental health' lays a special stress on the wholeness of human intuition, emotion, thought, and action.